Acclimation of Anaerobic Culture Degrading 2,4-Dichlorophenol and Its Biodegradation - Cheng, T.; Chen, C.; Pan, T. (Asian Journal of Chemistry, 2013)
The experiment was conducted to examine the biodegradation of 2,4-dichlorophenol (2,4-DCP) and the variation of COD concentration during the acclimation period of anaerobic microorganism. The effect of acclimation substrates and acclimated culture on the 2,4-DCP degradation was also investigated. The results showed that, the anaerobic microorganism had the potential of degrading chlorophenols. During the acclimation period, the anaerobic culture adapted to the toxicity of 2,4-DCP gradually. The degradation capability and degradation rate of 2,4-DCP improved with the extension of acclimation time. The 2,4,6-trichlorophenol (2,4,6-TCP) and 2,4-DCP acclimated culture for the 2,4-DCP degradation was superior to the 2,4-DCP acclimated culture during the acclimation period. The COD removal rate was enhanced with the long-term coexistence of 2,4,6-TCP and 2,4-DCP. Moreover, Compared to the fresh culture, the acclimated culture improved the 2,4-DCP degradation obviously and the optimal acclimated microorganism was the culture acclimated to 2,4,6-TCP and 2,4-DCP. The COD removal rate in different systems had a relation to the 2,4-DCP degradation in some extent.